Denials and defences in the law of unjust enrichment - Goudkamp, J; Mitchell, C (Hart Publishing, 2014)
In this chapter we argue that the rules governing the imposition of liability for unjust enrichment can be reduced to two categories. There are rules that define the elements of an action in unjust enrichment, and there are rules that specify situations in which liability will not arise, or will not arise in full, even though all of the elements of an action can be established. If this is correct, then it follows that there are two and only two types of response that a defendant can legitimately make with a view to avoiding or limiting his liability in unjust enrichment. He can argue that the claimant has failed to establish an element of his action. Or he can admit that the claimant has established all of the elements of his action but invoke a rule that wholly or partly exempts him from liability nonetheless. We term these responses ?denials? and ?defences? respectively. We then proceed to consider some possible rationales for dividing the liability rules in unjust enrichment between actions and defences. Finally, we examine whether certain of the defendant?s responses identified in Chapter 8 of the Restatement Third: Restitution and Unjust Enrichment, which is entitled ?Defenses to Restitution? and elsewhere in the Restatement are denials or defences. The analysis in this regard is descriptive rather than normative. Our aim is to determine how the responses under review should be classified in light of their presentation in the Restatement. We do not take a position on the normative issue of how particular responses ought to operate. That issue is best addressed once the descriptive analysis that we undertake here has been completed.